Stolnic Constantin Cantacuzino - a passerby ﬂeeting through waves of history (Confluenţe Bibliologice, 2025)
Stolnik Constantin Cantacuzino was a scholar, one of the most outstanding representatives of humanism in Wallachia at the end of the 17th century. His great passion, bibliophilia, eventually led to the formation of the famous library in Margineni.
Keywords: Cantacuzino Constantin (1639 – 1716); Romanian history